2015
DOI: 10.1371/journal.pntd.0003693
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Vaccine against Yellow Fever Virus: Development and Evaluation

Abstract: Attenuated yellow fever (YF) virus 17D/17DD vaccines are the only available protection from YF infection, which remains a significant source of morbidity and mortality in the tropical areas of the world. The attenuated YF virus vaccine, which is used worldwide, generates both long-lasting neutralizing antibodies and strong T-cell responses. However, on rare occasions, this vaccine has toxic side effects that can be fatal. This study presents the design of two non-viral DNA-based antigen formulations and the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 39 publications
1
29
1
1
Order By: Relevance
“…The study not only demonstrated protection and immunogenicity of the constructs, but also high apparent safety in mice, as the vaccines themselves were not neurotropic when administered at doses exceeding the that required to induce protection. A plasmid-vectored DNA vaccine was constructed by fusion-ligation of the 17DD substrain prM/M-E onto that of human LAMP-1, a strategy designed to target the antigen structural subunit for efficient trafficking to MHC-II compartments and consequent presentation and stimulation of cellular immune responses [75]. A 45 day, three-dose course of the LAMP-1 plasmid construct was protective when assayed in mice against live 17DD virus delivered intracerebrally.…”
Section: New Yfv Vaccine Candidate Technologies and Monitoring Of Safetymentioning
confidence: 99%
“…The study not only demonstrated protection and immunogenicity of the constructs, but also high apparent safety in mice, as the vaccines themselves were not neurotropic when administered at doses exceeding the that required to induce protection. A plasmid-vectored DNA vaccine was constructed by fusion-ligation of the 17DD substrain prM/M-E onto that of human LAMP-1, a strategy designed to target the antigen structural subunit for efficient trafficking to MHC-II compartments and consequent presentation and stimulation of cellular immune responses [75]. A 45 day, three-dose course of the LAMP-1 plasmid construct was protective when assayed in mice against live 17DD virus delivered intracerebrally.…”
Section: New Yfv Vaccine Candidate Technologies and Monitoring Of Safetymentioning
confidence: 99%
“…However, the decline in herd immunity and discontinuation of mosquito control measures in many parts of Africa are considered the major causes for the resurgence of yellow fever and periodic epidemics in East and West African countries during the last 2 decades (4). In addition, recent clinical studies also showed that an activated immune microenvironment with other microbial infections prior to vaccination impeded efficacy of the YFV-17D vaccine in an African cohort, suggesting that vaccine regimens may need to be boosted in African populations to achieve efficient protective immunity (5)(6)(7). It has been estimated that up to 1.7 million YFV infections may occur in Africa each year, resulting in 29,000 to 60,000 deaths (8,9) (http://www.who .int/csr/disease/yellowfev/yellowfeverburdenestimation _summary2013.pdf).…”
mentioning
confidence: 99%
“…In the U.S an inactivated 17D vaccine was produced and tested clinically but failed to go for commercialization 4 . Two non-viral DNA based antigens were also evaluated as vaccine candidates and revealed potency but further development studies are required 40 .Considering these factors, the idea of designing an alternative vaccine for yellow fever virus to replace or complement the existing live attenuated one can be pursued.…”
Section: Discussionmentioning
confidence: 99%